2021
DOI: 10.1186/s12902-021-00844-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of valsartan combined with α-lipoic acid on renal function in patients with diabetic nephropathy: a systematic review and meta-analysis

Abstract: Background Diabetic nephropathy (DN) is one of the most serious microvascular complications of diabetes, valsartan and α-lipoic acid alone or in combination has been used for the treatment of patients with DN. However, some results in these clinical reports were still controversial. The purpose of this study was to evaluate the efficacy of valsartan combined with α-lipoic acid on renal function in patients with DN. Methods We searched the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…Apart from the gut microbiota composition, the functions of the gut microbiota obviously vary in patients with T2DM and DN. Lipoic acid can reduce the level of urinary albumin and oxidative stress in patients with DN, improve antioxidant capacity, and protect kidney function ( 50 ). We have found elevated lipoic acid in DN patients, which suggests that the gut microbiota may affect drug metabolism as demonstrated in a previous study ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the gut microbiota composition, the functions of the gut microbiota obviously vary in patients with T2DM and DN. Lipoic acid can reduce the level of urinary albumin and oxidative stress in patients with DN, improve antioxidant capacity, and protect kidney function ( 50 ). We have found elevated lipoic acid in DN patients, which suggests that the gut microbiota may affect drug metabolism as demonstrated in a previous study ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even more, our subgroup analysis showed that 12 weeks (median) or shorter ALA supplementation significantly reduce CRP levels. On the other hand, results from a previously conducted meta-analysis by Saboori et al 32 showed that ALA supplementation caused significant CRP reduction when trial duration was more than 8 weeks (median), while subgroup analysis from Haghighatdoost and Hariri 33 study showed no significant CRP reduction when study duration was 9 weeks or longer (median). The observed differences between ours and other published meta-analyses regarding the duration-dependent effect of ALA on CRP levels should be attributed to the difference in the studies involved in the analysis.…”
Section: Discussionmentioning
confidence: 95%
“…The conducted meta-analysis revealed the influence that ALA has on lipid profile, male infertility, weight loss, glycemic control, and renal function in patients with diabetic nephropathy. 30 - 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations